Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1364/ome.442246
|View full text |Cite
|
Sign up to set email alerts
|

Quantum barriers with a polarization self-screening effect for GaN-based VCSELs to increase the electron-hole stimulated recombination and output performance

Abstract: Hole injection is one of the fundamental limitations that affect the lasing power for GaN-based vertical-cavity surface-emitting lasers (VCSELs). In this report, a GaN-based VCSEL with a composition gradient quantum barrier (CGQB) structure is proposed and investigated. The designed InxGa1-xN quantum barrier has a linear gradient level of InN composition along the [0001] orientation, which is effective in reducing the energy band barrier height for holes. Furthermore, the polarization-induced bulk charges that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Moreover, a previous study demonstrated that the QCSE can be minimized by incorporating quantum barriers with specific compositions of InGaN. These quantum barriers are designed to generate polarization-induced bulk charges, as determined through numerical simulations [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study demonstrated that the QCSE can be minimized by incorporating quantum barriers with specific compositions of InGaN. These quantum barriers are designed to generate polarization-induced bulk charges, as determined through numerical simulations [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%